CODE-SWITCHING IN INDONESIAN POPULAR SONGS AND THE IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING - Rahmawaty Kadir (Journal of Applied Linguistics and Literature)
Code-switching is a common phenomenon in a bilingual and multilingual society. People utilize codes in different forms of interactions for various reasons and functions. This paper investigates the types and functions of code-switching between English and Bahasa Indonesia that occur in lyrics. Fifteen Indonesian songs produced from 2009 to 2019 were examined. This analysis reveals that four types of code-switching occur in the lyrics of Indonesian popular songs: code-switching between sentences (intersentential), code-switching within sentences (intrasentential), code-switching involving changes of pronunciation, and emblematic code-switching. It further reveals that the functions of code-switching in the lyrics vary from discussing particular topics, lexical needs and availability, being emphatic, expressing group identity, simplifying words and expressions, and conveying a strong emotion/gaining attention.